Radiative transitions in solid C₆₀ under UV laser and VUV synchrotron radiation - Terekhin, M.A.; Svechnikov, N.Yu.; Kolmakov, A.A.; Stankevitch, V.G.; Stepanov, V.A.; Bezmelnitsin, V.N.; Kamada, M.; Tanaka, S.; Kan'no, K.; Ashida, M.; Matsumoto, T. (Физика низких температур, 1995)
Photoluminescent properties of pure C₆₀ thin solid films have been investigated in the emission range of 1.2-2.4 eV over a wide temperature interval under excitations with 3.7 and 36 eV photons. Dose dependence of the luminescence degradation of C₆₀ films under long-time UV and VUV irradiation has been discovered and examined at various ambient conditions. Temperature dependence of luminescence from 10 to 300 K exhibited a step-like peculiarity in the vicinity of the structural phase transition near Tc ~ 250 K, and a decrease from 13 to 10 K. Also a C₆₀ luminescence in the process of doping by neutral potassium atomic beam «in situ» at 400 K has been examined. The luminescence decay time measurements gave values of 1.2 ± 0.. I ns for a singlet excited state, and -400 microseconds for a triplet state, the latter decays non-radiatively with a probability of more than 80%. The experimental data obtained lead us to a conclusion that the intrinsic nature of luminescence in solid C₆₀ , correlates with the bulk properties which may be attributed, mainly, to self-trapped singlet excitons. The influence of the triplet state was also observable via protection against photopolymerization due to energy transfer from the excited triplet state of C₆₀ to intercalated dioxygen.